(untitled) (Research, Society and Development, 2020)
This research aims to identify environmental practices implemented by chemical laboratories of universities in order to enhance their dissemination. For that, a systematic literature review was carried out, taking into consideration three databases: Scopus, Web of Science and Scielo. Based on clear inclusion critera, 35 articles were selected from an initial sample of 2.514. The results evidenced 46 environmental practices implemented, which were categorised according to the environmental aspect or environmental management and control, namely: waste management, chemicals, environmental education, energy efficiency, conservation management, planning, infrastructure design and legal compliance. This review contributes to the knowledge hence other environmental practices are discussed beyond the traditional focus of the literature, i.e. chemical waste management. This includes other practices, for instance the management of chemical products, environmental awereness and as related to management and planning.